Selected elements of the logistic customer service in public transport – Gdynia case - Krzysztof Grzelec (Przegląd Komunikacyjny)
Relationship marketing involves negotiated service promise, which is characterized by: the reliability of trip in the desired direction, using of suitable means of transport at a cer-tain price, expected conditions of trip in right time. The universality of the principles of cus-tomer service determined the adoption of marketing orientation by the Public Transport Au-thority in Gdynia. It’s made by marketing research and forming of public transport services based on its results. PTA in Gdynia planning services, takes into account not only the needs of existing customers (passengers), but also the needs of people using private cars. This makes possible to increase quality of PT services. The rule: "right the first time" is the main determi-nant of Public Transport Authority in Gdynia.